Holocene macromammal remains from Grotta dell’Edera/Stenašca, Trieste Karst (excavations in 1990–2001) - Boschin, Francesco (Arheološki vestnik, 2020)
The zooarchaeology and taphonomy of large mammal remains from Grotta dell’Edera (Trieste Karst, northern Italy) are presented in this paper. A Mesolithic (Sauveterrian) Preboreal assemblage testifies to a first human occupation, followed by a second longer Sauveterrian frequentation from the Boreal until the beginning of the Atlantic. The last Mesolithic groups are represented by a Castelnovian assemblage, in which the bones of domesticates were detected with wild games remains. The presence of weathered bones in this layer indicates possible slow sedimentation, which may have led to the formation of a palimpsest, but more geoarchaeological data are needed to clarify this context. Neolithic and Eneolithic layers are characterized by an overwhelming presence of caprines and by an increase in the domestic pig and cattle through time. A number of caprine foetal remains points to the presence of individuals accumulated due to natural death and to the caution needed in evaluating caprine age profiles from sites used as stables.